Dimensional Analysis of Shear Stress of Blood Flow through a Bifurcation: Skin Friction Coefficients - Kanokjaruvijit, Koonlaya; Siripokharattana, Jirasak (Asian Health, Science and Technology Reports, 2016)
The purpose of the current work is to numerically study blood flow through a bifurcation in a model by using the finite element method. The calculated results are reported in terms of velocity contours, wall shear stress and skin coefficients for specific locations during a pulse cycle such as the peak systole and the diastole, for which the corresponding Reynolds numbers are 750 and 300, respectively. Three types of fluids were examined: blood using the Carreau-Yasuda model, water and air. The shapes of the wall shear stress and skin friction coefficient distributions were similar in all fluid types. However, values of skin friction coefficients for the three fluids were similar, and gave much lower percentage differences between the blood and both Newtonian fluids than wall shear stress values.